Formulation and Evaluation of Pediatric Azithromycin Suspension - MAMATHA JYOTHI ANCHA; K.L.SENTHIL KUMAR; D.D.JACKSON (International Journal of Pharma and Bio Sciences, 2010)
Pediatric Azithromycin Suspension were formulated by employing various suspending agents in hydroxyl propyl methyl cellulose, sodium corboxy methyl cellulose, acacia, gum tragacanth and were evaluated for particles size, physical stability and dissolution rate. Pediatric Azithromycin Suspension formulated by employing various suspending agents exhibited good suspendability and give higher dissolution rate than those formulated with Azithromycin. Good linear relationships were observed between particle size and dissolution rate & efficiency i.e., Smaller Particles gave higher dissolution rate and efficiency values.